(untitled) (Revista de Artes Marciales Asiáticas, 2019)
The International Academic Conference for Taekwondo (iACT) 2019 was held from February 17-18 at Stanford University. The two-day conference featured numerous taekwondo social science researchers and scholars from around the world and several international taekwondo organizations. iACT 2019 was the first time an academic conference on taekwondo–or any combat sport–was held at a world-renown, elite-level university. Holding iACT 2019 at Stanford University validated taekwondo’s researchers and their ideas and unquestionably legitimized taekwondo as an academic research field. This report outlines the conference’s events and summarizes the most poignant concepts presented at iACT 2019.